Factor Concentrates Usage in Hemophilia A Children: Comparison the Outcomes of Treatment within 2 Hours and 2-24 Hours after the Onset of Bleeding Symptom - Parapakpenjune, Surapan (Journal of Health Science of Thailand, 2018)
Hemophilia, an X-linked recessive bleeding disorder, is a lack of plasma protein that results in bruise or bleeding. In the past, patients must be hospitalized for blood component therapy when bleeding symptom occurred. Since September 2006, factor concentrates was distributed to patients for early bleeding therapy within 2 hours after bleeding symptom occurred. But some patients still were hospitalized again after the use of factor concentrates for early bleeding therapy. The objective of this study was to analyze the outcome of bleeding therapy with factor concentrates and duration between the onset of bleeding symptom and factor concentrates usage by retrospective data collection from September 2006 to February 2009 in children who were diagnosed with hemophilia from Maharat Nakhon Ratchasima Hospital. There were 24 eligible patients with major bleeding episodes of 362 times within two and a half years. Median annual bleeding episodes were 3.6, 8.0, 8.3 times (interquartile range 5.4, 9.7, 3.5), median factor concentrates used per episode were 9.6, 10.0, 10.9 unit.kg-1 (interquartile range1.9, 4.1, 7.2), median annual factor concentrates used were 51.9, 168.0, 99.2 unit.kg-1 (interquartile range 28, 109.7, 63.8), in mild, moderate, severe degree respectively. Factor concentrates used within 2 hours after the onset of bleeding symptom was possible among 42 percent of the samples. Hospitalization rate for blood component therapy was 1.9 percent. To compare the outcome of treatment with factor concentrates within 2 hours and 2-24 hours after bleeding symptom occurred, 1-sided Fischer’s exact test was used showing no significant difference between outcome of treatment with factor concentrates within 2 hours and 2-24 hours after bleeding symptom occurred within each group (mild, moderate, and severe groups). In decreasing hospitalization for blood component therapy, factor concentrates usage within 24 hours after bleeding symptom occurred was useful.